A comparative study of viruses associated with acute haemorrhagic conjunctivitis. Issue 4 (April 1974) - Higgins, P. G.; Scott, R. J.; Davies, Patricia M.; Gamble, D. R.
Abstract : Seven representative isolates from six outbreaks of acute haemorrhagic conjunctivitis were shown to have the characteristics of enteroviruses. Two viruses differed from the remaining five isolates in producing paralysis in suckling mice and being resistant to 2-hydroxybenzyl-benzimidazole. These two viruses were also closely related antigenically and distinct from the other five viruses which were serologically similar to each other. Neither group of viruses was inhibited by antisera to the known enteroviruses and they probably represent two new enterovirus types one related to the Coxsackie A viruses and the other to the echoviruses.